Degradation Structures of the Steels Applied in Energetics - Svobodova, Jaroslava; Lukáč, Ivan (Manufacturing Technology Journal, 2018)
Currently, it is in the power industry exerted the pressure in terms of environmental impact and economics. That means requirements focussed on the development of high efficiency and low emission systems. Both of these requirements leads to the increasing of the thermal efficiency of a power plant and that means also increasing of the working temperatures. In the future, it will be necessary to develop materials that can withstand these demanding conditions and requirements. Strength of steel used at high temperatures is one of the properties which affect the life time of the power equipment. These properties strongly depend on microstructure of material. However, useful initial microstructures are unstable in service conditions. The changes come gradually at temperature-dependent rate through processes of thermal degradation. Many of these processes are caused by changes in the carbide structure of the steels and other phase transformations.This contribution deals with the degradation structures of the steels applied in energetics.
Keywords: Degradation; Steels; Energetics; Microstructure; Carbides